2009
DOI: 10.1128/iai.00292-09
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Expression of the Haemophilus ducreyi LspB and LspA2 Proteins by CpxR

Abstract: The LspA1, LspA2, and LspB proteins of Haemophilus ducreyi comprise a two-partner secretion system that has been shown to be necessary for H. ducreyi to inhibit phagocytosis by immune cells in vitro. Inactivation of lspA1 resulted in increased levels of LspA2, suggesting that these two proteins are differentially controlled (C. J. Ward et al., Infect. Immun. 71:2478-2486, 2003). Expression of LspA2 but not LspA1 was shown to be both growth phase dependent and affected by the presence of fetal calf serum (FCS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
75
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(80 citation statements)
references
References 64 publications
5
75
0
Order By: Relevance
“…5B, double asterisks). 35000HP⌬cpxR, in which the Cpx regulon is constitutively inactive (29), showed no significant difference from 35000HP in survival of LL-37 at concentrations ranging from 0.2 to 20 g/ml (data not shown). Together, these data suggest that, although activation of CpxRA causes increased sensitivity to LL-37, the MTR transporter itself independently contributes to LL-37 resistance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5B, double asterisks). 35000HP⌬cpxR, in which the Cpx regulon is constitutively inactive (29), showed no significant difference from 35000HP in survival of LL-37 at concentrations ranging from 0.2 to 20 g/ml (data not shown). Together, these data suggest that, although activation of CpxRA causes increased sensitivity to LL-37, the MTR transporter itself independently contributes to LL-37 resistance.…”
Section: Resultsmentioning
confidence: 99%
“…We tested this hypothesis by examining mRNA expression levels of selected Cpx-regulated genes, including dsrA, ompP2B, and two additional genes known to be either upregulated (HD0281) or downregulated (HD1155) by activation of CpxRA (28). HD0281 encodes the putative major fimbrial subunit FimA, and HD1155 encodes LspB, which is required for secretion of the antiphagocytic factors LspA1 and LspA2 (29,52). qRT-PCR analysis showed that, relative to 35000HP, the mtrC mutant had increased transcriptional levels of fimA and ompP2B and decreased mRNA levels of lspB and dsrA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest documented example of gene regulation in H. ducreyi involved a heme acquisition system (18), and in a later study, mutant analysis indicated that inactivation of the lspA1 gene would cause increased expression of the LspA2 protein (61). The use of DNA microarray analysis and real-time reverse transcriptase (RT) PCR showed that several hundred H. ducreyi genes are differentially regulated in the presence of fetal calf serum (FCS), and subsequent experiments revealed that the H. ducreyi CpxR response regulator is involved in negatively controlling expression of the lspB-lspA2 operon (35). Two-component signal transduction systems (TCSs) typically comprise a membrane-bound sensor (histidine protein) kinase and a cytoplasmic response regulator (for reviews, see references 38, 65, and 69).…”
mentioning
confidence: 99%
“…The demonstration of a functional CpxR ortholog in H. ducreyi (35), together with the presence of a closely linked open reading frame (ORF) encoding a predicted at 4°C, after which they were incubated in primary antibody for 3 to 4 h at room temperature or overnight at 4°C. Membranes were then incubated for 1 h at room temperature in a 1:20,000 dilution of either goat anti-mouse IgG-horseradish peroxidase (IgG-HRP) or goat anti-rabbit IgG-HRP (Bio-Rad, Hercules, CA).…”
mentioning
confidence: 99%